Entre o erudito e o popular : a flauta transversal de Plauto Cruz na história do Choro (1940-20002) - Pompermaier, Alexandre (2014)
This research aims to make up a social and historical analysis of the musical genre Choro, pointing to north that characterizes it as a musical manifestation of classical and popular synthesis. It is an approach that part of their origins in the late nineteenth century, culminating in the fixation of the genre in the early decades of the twentieth century. Trajectory of changes, adaptations and additions that followed parallel with the transformation of Brazilian society. Walking by the same historical bias try to discuss the concepts of classical and popular Brazilian culture in order to enhance the reflections that this relationship dispute and had in Choro, assuming that music is a reflection of society and in inverse proportion to society their musical genres. In addition, we seek to understand the process of assimilation and incorporation of these social and sound elements in Choro as responses to gaps still present in the historiography of gender that addresses how uniquely popular musical cultural event, without considering the elements of classical strand. In this same perspective has been the insertion of the transverse flute in analytic discourse because it is a characteristic instrument of its kind, which marked his sound on wheels Choro since the late nineteenth century becoming indispensable for his solo character. An authentic link between the cultures of classical and popular in Choro that began by Callado and Reichert in the first moments of the history of the genre sound representation. These, in turn, set the groundwork for this flute language reflected in the works of numerous composers and flutists of several later generations as Patápio Silva, Pixinguinha, Benedito Lacerda, Carrilho and Plauto Cruz himself. The "Wizard of the Flute", how is known the flutist and rio-grandense composer Plautus Cruz presents in his works in the historical heritage of this synthesis of popular and classical, both with regard to the language of the flute in Choro, as applied to their training and experience in your regional reality of Rio Grande do Sul. A legacy that transcends geographic lines the southern state and places it as one of the representatives of Choro nationally, such a representation in this compositional and interpretive scenario. Finally, the tension is to introduce the reader as it is this process of crystallization of these elements scholar and popular in Choro by the flute, analyzing directly part of the work of the composer and flutist Plauto Cruz. This work that consists of music and audio, reflecting a recent production dating from the late 1970s until 2002